Aquatic plant diversity of lakes around Gondia city, Maharashtra, India - Badole, Amol; Zode, Ravindra; Tagade, Walay; Kawale, Mahesh (2021)
Gondia is one of the centrally located districts of India. It is famous for its lakes and water bodies. These water bodies exhibit enormous diversity of plants according to geographical location, depth of water body, water regime, chemistry of water, soil and sediment characteristics. Very little work has been done so far on the flora of the water bodies of Gondia district. Therefore, a study has carried out to understand the aquatic plants diversity of selected 5 lakes around Gondia city. For this, well-planned surveys were carried out at selected sites frequently. During visits, data like habit, life span, local names, and life forms of all the plant species present in the water body were collected. During the study, 44 species of 37 genera belonging to 26 families have been recorded from selected sites. Most dominant family was Hydrocharitaceae with 4 genera and 4 species, followed by Asteraceae, Poaceae, Convolvulaceae and Potamogetonaceae with 3 species each. Jaccard and Sorenson similarity indexes showed that Lake I and Lake II have maximum similarity and highest diversity as compared to other sites. The present work revealed the database of aquatic plants in water bodies around Gondia, which will help in future work for the conservation, preservation and growth of the local biodiversity.
Bibliografija: 43 jed.
Abstract.
Keywords: Vodene biljke -- Bioraznolikost -- Močvare